Enhancing multiculturalism through culturally responsive teaching: Evidence from local history learning in metro city senior high schools - Amboro, Kian; Warto; Sariyatun; Purwanta , Hieronimus (Journal of Interdisciplinary Studies in Education, 2026)
This study addresses the limited integration of affective dimensions in Indonesian history education, which often prioritizes cognitive mastery over fostering students’ multicultural awareness. To address this gap, this research examines the effectiveness of culturally responsive teaching (CRT)-based local history materials in enhancing students’ multicultural attitudes. Using a quantitative quasi-experimental design involving 364 senior high school students in Kota Metro, an experimental group taught with CRT-based materials and a control group taught with conventional textbooks were compared. Data were collected using pretests and posttests with a validated Likert-scale instrument measuring tolerance, solidarity, respect for cultural differences, and inclusiveness. The findings reveal a significant improvement in the experimental group’s multicultural attitudes, reflected by higher gain scores and strong positive correlations between perceptions of CRT and attitude enhancement. The study concludes that CRT-based history instruction effectively strengthens empathy, intercultural understanding, and civic awareness, offering practical strategies for fostering multicultural competence in Indonesia’s classrooms.